The Influence of Principal Leadership and Teacher Performance on The Quality of State Junior High School Education in Tebing Tinggi District - Sartika, Endang; Destiniar, Destiniar; Harapan, Edi (Universitas Wiralodra, 2024)
This study aims to analyze the influence of principal leadership and teacher performance on the quality of education in State Junior High School in Tebing Tinggi District. The research method used is quantitative with a survey approach. The population of this study was all teachers and principals of state junior high schools in Tebing Tinggi District, with a random sample. Data was collected through questionnaires that had been tested for validity and reliability. Data analysis was carried out using multiple linear regression to see the contribution of each independent variable to the quality of education. Some people who face the quality of the Negeri Junior High School students in Kei Tebing Tinggi District are significant in the principal leadership and teachers' performance. This is known from the F-count = 16.452 > F-table 1.738 and can contribute 25.3% of the total number of factors, the remaining 74.7% due to other factors not mentioned in the study. The results of the study show that the leadership of school principals has a significant influence on the quality of education. School principals who apply transformational leadership styles tend to be able to increase teacher motivation and performance, which in turn has a positive impact on the quality of education. In addition, teacher performance was also found to have a significant influence on the quality of education. Teachers with good professional, academic, social, and personality competencies can create an effective and efficient learning process, thereby improving the quality of education in schools. In conclusion, the principal's leadership and teacher performance significantly improved the quality of education at State Junior High Schools in Tebing Tinggi District. Therefore, it is recommended that schools and local governments continue to strengthen the leadership capacity of school principals and improve teacher performance through continuous training and professional development.